1991
DOI: 10.1007/bf02244564
|View full text |Cite
|
Sign up to set email alerts
|

Separate and combined effects of the social drugs on psychomotor performance

Abstract: Ten female subjects (five smokers and five non-smokers) performed a choice reaction time task (CRT), a compensatory tracking task (CTT), a short-term memory task (STM) and were tested for their critical flicker fusion threshold (CFF) at set points over 4 h after the administration of each possible combination of nicotine (2 mg gum or placebo), caffeine (250 mg capsule or placebo) and alcohol (30 g or placebo). Memory and motor function were shown to be facilitated by nicotine or caffeine, and the debilitating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
63
8

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 36 publications
12
63
8
Order By: Relevance
“…Mitchell et al 1995;Glautier et al 1996). Alternately, individuals may use nicotine to counteract alcohol's debilitating effects on cognitive skills (Kerr et al 1991;Madden et al 1995). Relatedly, there is evidence that alcohol may act as a cue for tobacco use in both laboratory (Gulliver et al 1995) and field (Shiffman et al 1994) settings.…”
Section: Alcohol-tobacco Comorbiditycontrasting
confidence: 40%
“…Mitchell et al 1995;Glautier et al 1996). Alternately, individuals may use nicotine to counteract alcohol's debilitating effects on cognitive skills (Kerr et al 1991;Madden et al 1995). Relatedly, there is evidence that alcohol may act as a cue for tobacco use in both laboratory (Gulliver et al 1995) and field (Shiffman et al 1994) settings.…”
Section: Alcohol-tobacco Comorbiditycontrasting
confidence: 40%
“…Some studies demonstrated cognitive improvements in smokers in the absence of withdrawal effects (Warburton and Arnall, 1994). In non-smokers nicotine enhanced motor responses in brief tests of attention (Kerr et al, 1991) and performance in tests of sustained attention (Foulds et al, 1996;Levin et al, 1998;Mumenthaler et al, 1998). In contrast, other studies reported that nicotine either had no effect or impaired performance in non-smokers or non-abstinent smokers in tasks measuring sustained or selective attention (Heishman and Henningfield, 2000;Heishman et al, 1993;Hindmarch et al, 1990).…”
Section: Introductioncontrasting
confidence: 41%
“…46,47 This study provided little evidence that the effects of nicotine are influenced by concurrent caffeine (with the exception of working memory accuracy as noted above) and is consistent with other studies examining the combination of these drugs in nonsmoking, moderatecaffeine-consuming individuals. 21,22 This observation may suggest that the coadministration of tobacco and caffeine-containing beverages reflects a behavioral rather than pharmacological mechanism. Sensory characteristics associated with common nicotine and caffeine vehicles (ie, cigarettes, coffee) can influence self-administration.…”
Section: Discussionmentioning
confidence: 44%
“…19,20 Accordingly, there are several reports of the combined effects of nicotine and caffeine in nonnicotine users (N = 10). 21,22 However, these small-sample studies may have been underpowered. Thus, their failure to report an enhanced effect of the nicotine/caffeine combination, relative to either drug alone, may reflect a Type II error.…”
mentioning
confidence: 48%